Handbook of crystal growth. Vol. III, - Kuech, Tom (Elsevier Science, 2014)
Volume IIIA Basic Techniques Handbook of Crystal Growth, 2nd Edition Volume IIIA (Basic Techniques), edited by chemical and biological engineering expert Thomas F. Kuech, presents the underpinning science and technology associated with epitaxial growth as well as highlighting many of the chief and burgeoning areas for epitaxial growth. Volume IIIA focuses on major growth techniques which are used both in the scientific investigation of crystal growth processes and commercial development of advanced epitaxial structures. Techniques based on vacuum deposition, vapor phase epitaxy, and liquid an.- Resumé vydavatel
Keywords: růst krystalů; crystal growth; elektronické knihy; sborníky; příručky; electronic books; papers of several authors; handbooks and manuals